Phenotypic diversity in beta-HbE thalassemia patients - Pustika Amalia Wahidiyat; Djajadiman Gatot; Tenny Tjitrasari; Harapan Parlindungan Ringoringo; N S Marzuki; R A Taufani; I Setianingsih; A Harahap (Paediatrica Indonesiana, 2006)
Background Thalassemia is a monogenic disease, yet the clini-cal manifestations (phenotype) are variable although they havethe same genotype. The clear-cut correlation between genotypeand phenotype in Î²-thalassaemia/HbE patients remains unex-plained. There are several factors that play a role in the severity ofthe clinical manifestations, i.e. two alpha-gene deletion, homozy-gote Xmn1 polymorphism +/+, -+-++, ++-++ haplotype, and hemo-globin Constant Spring.Objective To understand the clinical diversity of patients with HbE/Î± thalassemia and to determine whether it is possible to predictphenotypic severity from genetic factors.Methods A descriptive study on clinical presentations and hema-tological data of beta-HbE thalassemia patients. DNA analysis wasperformed to detect Î²-thalassemia mutations and the amelioratingfactors (alpha-globin genes deletions and Xmn1 restriction site poly-morphism at position â€“158 upstream of the G Î³-globin gene) whichwere already known.Results Thirty patients with HbE/Î² thalassemia (4 to 29 years old)were recruited. IVS1-nt5 (G>C) severe Î² + mutation was detectedin 20 patients. Eighteen of 20 patients with positive IVS1-nt5 mu-tation group were heterozygous for Xmn1 restriction site polymor-phism and none of the patients was co-inherited with two Ã¡-globingene deletion. Almost all patients (19/20) with positive IVS1-nt5mutation group required regular transfusions, yet the mean age atfirst blood transfusion was older in negative IVS1-nt5 mutation groupthan that of positive IVS1-nt5 mutation group (5.7 vs 4 years). Meanhemoglobin before initial transfusion was higher in negative IVS1-nt5 mutation group than that of positive IVS1-nt5 mutation group(5.88 vs 5.39 g/dl). The mean total transfusion per year was lowerin the negative IVS1-nt5 mutation group than that of positive IVS1-nt5 mutation group (190.6 vs 215.1 ml/year).Conclusions Beta-HbE thalassemia patients with identical betathalassemia mutation (IVS1-nt5) show remarkable clinical diver-sity. Neither two alpha-gene deletion, nor the Xmn1- G Î³ polymor-phism can explain the phenotypic variation. Other amelioratingdeterminants or genetic modifications responsible for the variableclinical severity remain to be explored.